36=x(12-3)

Simple and best practice solution for 36=x(12-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=x(12-3) equation:


Simplifying
36 = x(12 + -3)

Combine like terms: 12 + -3 = 9
36 = x(9)

Reorder the terms for easier multiplication:
36 = 9x

Solving
36 = 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
36 + -9x = 9x + -9x

Combine like terms: 9x + -9x = 0
36 + -9x = 0

Add '-36' to each side of the equation.
36 + -36 + -9x = 0 + -36

Combine like terms: 36 + -36 = 0
0 + -9x = 0 + -36
-9x = 0 + -36

Combine like terms: 0 + -36 = -36
-9x = -36

Divide each side by '-9'.
x = 4

Simplifying
x = 4

See similar equations:

| 6y-20y= | | 9(m+2)=9m+18 | | 4r^2+11r+6=0 | | -5x+4=-40 | | 1.07/x=15/100 | | D=x(f-d) | | f(x)=cos^5x | | tanx=0.2 | | 5-[-2]= | | x^4-6x^3-9x^2-54x-162=0 | | 5(x-8)=-42+5x | | 3y^2+3y+6=0 | | 2(n-8)-n=n-16 | | 7b^2+29b-30=0 | | -112=-27-5x | | -4(6a-2)= | | 90(x+24)+90(x)=4x(x+4) | | 14.5y=6 | | 21nx-3=0 | | 7a+2=5a+3 | | 7x-10=3(x-2)+5(x-1) | | 95=-47-4(t+6) | | -2x+9y=-6 | | 10-6x-9x+3= | | 8(2c+2)= | | 27(x-1)=3(2x) | | 8y+56=15y | | 20-2v=3v | | 90(x+4)+15(x)=4x(x+4) | | 30+x=7x | | 3y=-15x+270 | | -38+8x=2(8x+1)+8 |

Equations solver categories